2009
DOI: 10.1111/j.1750-3841.2009.01199.x
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic Acid Phenethyl Ester, an Antioxidant from Propolis, Protects Peripheral Blood Mononuclear Cells of Competitive Cyclists against Hyperthermal Stress

Abstract: Hyperthermal stress and resulting free radical generation is known to impair endurance capacity and immune cell redistribution during prolonged exercise. Caffeic acid phenethyl ester (CAPE), a phenolic compound purified from propolis, has many biological and pharmacological activities including antioxidation. To examine whether CAPE has protective effect against hyperthermal stress in athletes, we isolated peripheral blood mononuclear cells (MNC) from competitive cyclists and assessed their response to hyperth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 19 publications
1
25
0
1
Order By: Relevance
“…In humans, CAPE (1, 2 and 4 g/ml) showed protective effect against hyperthermal stress in athletes, enhancing the hyperthermal tolerance in immune mononuclear cells of competitive cyclists (Chen et al, 2009). Since the modern life comprises a wide range of stressful conditions, these preliminary results point out the importance of further research in order to understand propolis usefulness during stress and for the development of new medicaments.…”
Section: Propolis Immunomodulatory Actionmentioning
confidence: 97%
“…In humans, CAPE (1, 2 and 4 g/ml) showed protective effect against hyperthermal stress in athletes, enhancing the hyperthermal tolerance in immune mononuclear cells of competitive cyclists (Chen et al, 2009). Since the modern life comprises a wide range of stressful conditions, these preliminary results point out the importance of further research in order to understand propolis usefulness during stress and for the development of new medicaments.…”
Section: Propolis Immunomodulatory Actionmentioning
confidence: 97%
“…The authors found these to be efficacious. Chen et al [20] reported that pretreating of cyclists with propolis extract reversed or reduced the hyperthermiainduced effects, including reduced cell death, inhibition of the overproduction of superoxide, and an attenuation of the depletion of glutathione in the exercising cyclists. Wang et al [21] worked and reported on the use of bee pollen.…”
Section: International Journal Of Zoologymentioning
confidence: 99%
“…They do not possess sweat glands [2,3]. Environmental temperature in South-Western Nigeria is often higher than [18][19][20][21] • C [4] recommended for optimal productivity of growing broiler chickens [5]. Often, growth and welfare of the birds are compromised [6][7][8][9] and survival lowered [10] because of the birds responses to the stressor.…”
Section: Introductionmentioning
confidence: 99%
“…Propolis has anti-microbial, anti-inflammatory and antioxidant pharmacological properties (Nieva Moreno et al, 1999). Propolis, especially its compound CAPE (Caffeic Acid Phenethyl Ester), is used in research on heat stress mitigation, as it improves thermal tolerance (Chen et al, 2009). The antioxidant, cytostatic, antimutagenic, and immunomodulatory properties of propolis are based on its rich flavonoid, phenolic acid, and terpenoid contents (Kimoto et al, 1999;Wang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%